Isolation and Identification of Biosurfactant Producing Bacteria from Soil Aroundthe Gathering Station-Eor Plant PT. Bumi Siak Pusako – Pertamina Hulu - Gultom, Susi Susanti; M. Hasbi, M. Hasbi; Purwanto, Eko (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTOil spilled polluted soil present around the Gathering Station (GS) pool of the PT. Bumi Siak Pusako – Pertamina Hulu. The presence of the oil may trigger gene mutation in specific bacteria in that area and they become able to produce biosurfactant for degrading the oil. A study aims to obtain the biosurfactant producing bacteria was conducted in April 2018. 100 grams of polluted soil samples were taken from the area around the Gathering Station pool. The soil was grinded and mixed with 40 ml Brain-Heart Infusion (BHI) media, and then was incubated for 1 x 24 hours. The bacteria were then grown using Blood Agar media and then was purified using MacConcey media. The pure bacteria were tested (biochemical and emulsification tests). Morphological and biochemical characteristics shown that there were 5 species of bacteria, namely Escheria coli, Pseudomonas aeroginosa, Bacillus careus, Proteus sp. and Klebsiella sp. Result of Emulsification index shown that all bacteria obtained were potencial for producing biosurfactant.Keywords: Oil spill, Escheria, Pseudomonas, Bacillus, Proteus, Klebsiella